Evaluation of tillage systems on physical-chemical and microbiological properties in an Inceptisoil - García R., Dayra Yisel; Cárdenas H., Julian Fernando; Silva Parra, Amanda (Revista de Ciencias Agrícolas, 2018)
Based on the negative effects of conventional tillage in Inceptisoil at Villanueva, department of Casanare, Oriente of Colombia, the present investigation evaluated the impact of three tillage systems: T1: Reduced tillage (brushcutter, vibratory chisel, harrowing and sowing), T2: direct sowing and T3: conservation tillage (brushcutter, vibratory chisel, sowing with 30% crop residues) on some physical, chemical and biological soil variables, such as bulk density (Da ), porosity (ɲ), percentage of soil organic matter (%SOM) and colony forming units of fungi and bacteria CFUs. A completely randomized block design was used with three treatments and five repetitions for 15 experimental units, evaluated in two periods: M1: before preparation and M2: after two months of corn sowing. Analysis of variance and Tukey’s mean comparison test (p≤0.05) was performed. The Da was higher in T1 (1.52g/cm3) in M1. The T3 got the lower Da in both seasons (1.27g/cm3) and a greater porosity without differences between samplings. The T2 produced the higher percentage of SOM in M2. T3 showed higher CFUs of fungi and bacteria with respect to T1 and T2. Conservation tillage must be taken into account for a better soils management.